Pengaruh Kepemimpinan Kepala Sekolah Terhadap Motivasi Kerja Guru se Kecamatan Modoinding di Masa Pandemi Covid19 - Tombokan, Sarah; Sumilat, Margareta O (Jurnal Civic Education: Media Kajian Pancasila dan Kewarganegaraan, 2021)
The purpose of this study was to determine the effect of the principal's leadership on the work motivation of elementary school teachers in Modoinding district and to find out how much influence it had. The results of the research conducted show that based on the results of the calculation of the significance test and the linearity regression test above, it can be concluded that the influence of the Principal's Leadership (X) on the Teacher Work Motivation variable (Y) is significant and linear. This is evidenced because Fcount 7.913> Î± (0.05). Furthermore, the regression equation Å¶ = 37.299 + 0.297 X shows that every one increase in the Principal Leadership score will cause an increase in the Teacher Work Motivation score of 0.297 at a constant of 37.299. Based on the table above, it is known that the amount of Principal Leadership on Teacher Work Motivation in Modoinding District can be 0.150 or 15 percent. This indicates that 15% of the Principal's Leadership determines the Work Motivation of Teachers in Modoinding District. Meanwhile, 85% is influenced by other factors not examined.The more principals in Modoinding District carry out their functions optimally as school managers during the Covid19 pandemic, the more teachers' work motivation will increase, where the increase is linear.